Evolving international management systems: transgenic polities and transparency challenges in realpolitik space in 2050 - Caro, Denis H. J. (Université d'Ottawa | University of Ottawa, 2010)
﻿This paper posits that transgenic system forces are evolving and will engage future international management leaders in a multi-polar world of 2050. Social governance will be a cogent and compelling force in a tomorrow’s internationalized world community. This is a call to international management academicians and transformational leaders to understand and engage themselves in the underlying different perceptions and paradigms, or Weltanschauung, of diverse sectors in a world of rising new cultures. They must become "transgenic" in their perspective and seize every opportunity to develop and sensitize themselves to the socio-political dynamics that influence future growth and development of international management systems. An understanding of strategic transgenic forces and challenges serves as an inter- organizational learning paradigm, which fosters innovation and social responsibility for the betterment of humankind internationally.
Keywords: transparency challenges; chaotic systems; context analysis; organizational ecology; transgenic systems; international management systems